Organic residues as immobilizing agents in aided phytostabilization: (I) Effects on soil chemical characteristics - Alvarenga, Paula (2013)
A greenhouse experiment was conducted to evaluate the effect of three different organic residues, sewage sludge (SS), municipal solid waste compost (MSWC), and garden waste compost (GWC), as immobilizing agents in aided phytostabilization of a highly acidic metal-contaminated soil, affected by mining activities, using perennial ryegrass (Lolium perenne L.). The organic residues were applied at 25, 50 and 100 Mg ha−1 (dry weight basis), and their effects on soil chemical characteristics and on relative plant growth and metal concentrations were assessed. All the organic residues tested immobilized Cu, Pb and Zn, decreasing their mobile fractions. This was corroborated by negative correlations obtained between mobile Cu, Pb and Zn and other soil chemical characteristics, which rose as a consequence of the amendments applied (i.e., pH, electrical conductivity, organic matter, nitrogen content, available P and available K), and by the multivariate exploratory techniques performed that showed an inverse correlation between these groups of variables. The greatest increase in ryegrass relative growth (more than three times) was obtained in the presence of 50 Mg MSWC ha−1, followed by SS at the same application dosage. GWC did not contribute to an increase in shoot growth, due to its small capacity to correct soil acidity and to supply essential macronutrients (N, P, K). No extractant was able of demonstrating by a linear correlation the uptake of Cu, Pb and Zn by ryegrass. This plant was therefore not a good “indicator” of Cu, Pb and Zn availability in the soil. The results obtained in this study suggest that ryegrass can be used in aided phytostabilization for this type of mine contaminated soils and that MSWC, and to a minor extent SS, applied at 50 Mg ha−1, were effective in the in situ immobilization of metals, improving soil chemical properties and leading to a large increase in plant biomass.